Ectodysplasin target gene Fgf20 regulates mammary bud growth and ductal invasion and branching during puberty - Elo T; Lindfors PH; Lan Q; Voutilainen M; Trela E; Ohlsson C; Huh SH; Ornitz DM; Poutanen M; Howard BA; Mikkola ML (NATURE PUBLISHING GROUP, 2022)
Mammary gland development begins with the appearance of epithelial placodes that invaginate, sprout, and branch to form small arborized trees by birth. The second phase of ductal growth and branching is driven by the highly invasive structures called terminal end buds (TEBs) that form at ductal tips at the onset of puberty. Ectodysplasin (Eda), a tumor necrosis factor-like ligand, is essential for the development of skin appendages including the breast. In mice, Eda regulates mammary placode formation and branching morphogenesis, but the underlying molecular mechanisms are poorly understood. Fibroblast growth factor (Fgf) receptors have a recognized role in mammary ductal development and stem cell maintenance, but the ligands involved are ill-defined. Here we report that Fgf20 is expressed in embryonic mammary glands and is regulated by the Eda pathway. Fgf20 deficiency does not impede mammary gland induction, but compromises mammary bud growth, as well as TEB formation, ductal outgrowth and branching during puberty. We further show that loss of Fgf20 delays formation of Eda-induced supernumerary mammary buds and normalizes the embryonic and postnatal hyperbranching phenotype of Eda overexpressing mice. These findings identify a hitherto unknown function for Fgf20 in mammary budding and branching morphogenesis.